PROBLEMATIKA PENDIDIKAN ISLAM DI INDONESIA - Siti Suwaibatul Aslamiyah (Al Hikmah: Jurnal Studi Keislaman, 2013)
Education as an important factor in the process of development and progress of human life, a very dominant center of attention from all walks of society, especially those who have the authority to develop, so that a variety of methods are used to develop it. However, that did not run smoothly and seamlessly as there are a variety of obstacles and problems that become an obstacle smooth the business, especially at a time like now, in the midst of the complexity of the problems of the nation and the state.Therefore, in the article entitled "Problems of Islamic Education in Indonesia," the authors sought review of the problems faced and their Islamic education in Indonesia it appears logical alternative solutions to these problems. As a conclusion of this paper is that the problem-permsalahan being faced by today's Islamic education is a range of quality and quality of Islamic education are less in sync with the needs of the community and are less responsive to the demands of the workplace. With such circumstances, attempts to do is to Islamic education system should be reformed, direaktualisasi, and innovated in order to resolve themselves with mesyarakat dynamics and can meet the demands and needs of society and the free market era of regional autonomy